Characterization of whey protein isolate-(−)-epigallocatechin-3-gallate conjugates prepared by non-enzymatic and enzymatic methods and their application in stabilizing β-carotene emulsion. (15th January 2023) - Chen, Weijun; Zhu, Jiayu; Wang, Wenjun; Liu, Dayu; Zhang, Yin; Li, Yuncheng; Meng, Fanbing; Zhang, Wei; Liu, Donghong
Highlights: Both EGCG conjugation and conjugation method affect the structure of WPI. The highest grafting efficiency was obtained by tyrosinase-catalyzed oxidation. The conjugates showed better emulsifying and antioxidant activity. The antioxidant activities of conjugates are proportional to their EGCG content. β-Carotene stability was positively correlated with EGCG content in conjugates. Abstract: (−)-Epigallocatechin-3-gallate (EGCG) was conjugated to whey protein isolate (WPI) using alkaline treatment, free radical grafting and tyrosinase-catalyzed oxidation. The structure and properties of the obtained conjugates and their application as antioxidant emulsifiers in stabilizing β-carotene emulsion were systematically characterized. Fourier transform infrared spectroscopy and sodium dodecyl sulfate–polyacrylamide gel electrophoresis verified the covalent linking between WPI and EGCG. The highest grafting efficiency was obtained for enzyme conjugate, followed for alkaline conjugate. Conjugation of EGCG decreased the α-helix content and fluorescence intensity of protein, and these changes depend on both EGCG conjugation and the cross-linking methods. Due to their improved emulsifying properties and antioxidant activity, WPI-EGCG conjugates formed smaller emulsion droplets and protect the encapsulated β-carotene more effectively, and the protective property is positively correlated with EGCG content in conjugates.